Public Awareness of Low-Carbon Economy in Nigeria: A Case Study of Akwa Ibom State - EE Etim; JE Asuquo; FA Gabriel (Journal of Applied Sciences and Environmental Management)
This paper aims to examine levels of awareness and performance relating to the promotion of a Low-carbon economy (LCE) among the general public in Akwa Ibom State, Nigeria. The data and information used were derived from 600 questionnaires distributed randomly among households in North West, North East and South senatorial districts of Akwa Ibom State. The results indicate a combination of high awareness with poor understanding of LCE programmes among respondents, with the poor understanding probably due to a shortage of appropriate information from trusted sources and shortcomings in education. Respondents generally showed positive attitudes toward pro-environmental actions, such as refusing to use plastic bags, waste recycling, water and energy conservation. Apart from regulation and policies, they considered education and economic incentives as effective mechanisms to promote LCE implementation. Overall, those consulted responded favourably towards the prospect of LCE. Results of the study, at this preliminary stage, suggest that the general public in Nigeria has the potential to be a facilitator of environmental improvements in the country. @JASEM